Optimization of sintering and heat treatment parameters for improved toughness of additively manufactured steel with site specific composition - Chiang, Po-Ju (2025)
The ability to freely modulate the composition of a material at different locations in a part presents designers with an important tool for engineering the desired properties for different applications. By controlling the degree of deposition of carbon-loaded inks in binder jet 3D printing at different spatial points, steel parts with site-specific concentrations of carbon can be easily produced. The sintering process for such 3D printed parts, however, presents a conundrum – high sintering temperatures and long sintering durations lead to high relative densities and better mechanical properties, but also cause extensive diffusion of carbon throughout the part, which will distort the intended site-specific compositional design. To overcome this limitation, we first constructed a model based on the semi-empirical Master Sintering Curve to analytically evaluate the sintering parameter space for high relative density and sharp compositional contrasts. The model indicated that the optimization point lies with a high temperature and short duration, which were validated experimentally. Going further, we investigated the mechanical properties of the optimally sintered steel under various carbon loading and showed how the austenitizing temperature of steel decreased with increasing carbon content. Therefore, by selecting a post-sintering heat treatment temperature that lies between the austenitizing temperature of high carbon and low carbon steel, the regions with high carbon content can be selectively austenitized and quenched to form martensite. Using finite element simulations, which were then experimentally validated, we designed a cuboid part with a central hole and showed how selective carburization of the hole perimeter can lead to a relocation of the failure point away from the hole, thereby improving the toughness of the site-specific sample (51.8 J/m3) over its homogeneous counterparts (3.4 J/m3 for high carbon steel, and 17.1 J/m3 for low carbon steel).